A robust metal-free electrocatalyst for nitrate reduction reaction to synthesize ammonia. (July 2021) - Li, Y.; Xiao, S.; Li, X.; Chang, C.; Xie, M.; Xu, J.; Yang, Z.
Abstract: Electro-synthesis of ammonia at ambient environment is a promising alternative of the industrial Haber-Bosch process operated under critical conditions. In this work, we have systematically investigated the electro-reduction of nitrate (NO3 − RR) to ammonia catalyzed by fluorine doped carbon (FC) synthesized from the pyrolysis of the discarded cigarette filter saturated with polytetrafluoroethylene (PTFE) solution. FC electrocatalyst shows an exceptional NO3 − RR catalytic performance with Faradaic efficiency of 20% associated with ammonia production rate of 23.8 mmol h −1 gcat −1, 2 and 4-fold better than bare C electrocatalyst. Furthermore, a stable NO3 − RR activity is also achieved for FC electrocatalyst. Density functional theory (DFT) results suggest that F dopants efficiently reduce the energy barriers of NO3 − hydrogenation and suppress the competitive hydrogen evolution reaction (HER). This observation will be beneficial for constructing a high-performance metal-free electrocatalyst to electro-synthesize ammonia from NO3 − RR. Graphical abstract: Image 1 Highlights: FC is a superior electrocatalyst for nitrate reduction reaction to ammonia. Faradaic efficiency of FC is 2-fold higher than bare C electrocatalyst. F dopants induce a 4-fold higher ammonia yielding rate.